Journey to Grow: Linking Process to Outcome in Target Site Selection for Cannabis Cultivation. (February 2013) - Bouchard, Martin; Beauregard, Eric; Kalacska, Margaret
Objectives: To test whether there is a relationship between characteristics of the journey to an outdoor cannabis cultivation site and the total number of plants grown. Methods: Spatial data on the location of a sample of 132 cultivation sites derived from aerial detection policing efforts is used. TwoStep cluster analysis is employed to derive profiles of cultivation sites based on three measures of distance (i.e., distance to road, to water, and elevation) and regression analysis is used to examine their implications for the number of plants grown. Results: Four types of cultivation sites are found: prime, rugged, dry, and remote . Prime sites are fairly close to roads and water sources and are at relatively low elevation. They grow the greatest number of plants (mean = 171). Low elevation is the single most important factor correlate of operation size. Further, remote sites (both further from road and at higher elevation) tend to be larger. Conclusions: A majority of growers are capable of identifying "prime" locations in which the tradeoff between rewards and security appears to be maximized. This study is limited by the fact that there was no information available on the offenders themselves. Future research should employ interviews to clarify decision-making processes.